New species of Neocorynura Schrottky from Brazil (Hymenoptera: Apoidea) - Gonçalves, Rodrigo Barbosa (Zootaxa, 2019)
Neocorynura Schrottky is one of the most speciose genera in the Augochlorini with about 80 species. Neocorynura is primarily distributed in the Neotropical region, from Argentina to Mexico. New species have been described recently, but the Brazilian fauna has not been studied at the same rate. Thus, the objective of this study is to provide a revision of Neocorynura species from Brazil. More than 2,500 specimens were studied along with the examination of primary type specimens and/or high resolution photographs of type material. A total of 44 species were recognized, 24 new species are added to the fauna and figured as N. acuta sp.nov., N. aethra sp.nov., N. amabilis sp.nov., N. arethusa sp.nov., N. aurantia sp.nov., N. carmenta sp.nov., N. dictyata sp.nov., N. eliasi sp.nov., N. hebe sp.nov., N. hyalina sp.nov., N. insolita sp.nov., N. laevistriata sp.nov., N. lamellata sp.nov., N. meloi sp.nov., N. nambikwara sp.nov., N nicolle sp.nov., N. olivacea sp.nov., N perfida sp.nov., N. pilosifacies sp.nov., N. proserpina sp.nov., N. rubicunda sp.nov., N. surrufa sp.nov., N. truncata sp.nov., and N. veneta sp.nov. I designate the lectotype for Corynura oiospermi Schrottky and consider this name as a junior synonym of Halictus codion Vachal. Augochloropsis celaeno Schrottky is considered a junior synonym of Corynura pseudobaccha Cockerell. Casosoma semimarginata Cockerell is resurrected from synonymy with Cacosoma aenigma Gribodo. Neocorynura aenigma (Gribodo) and Neocorynura caligans (Vachal) are removed from the faunal list for Brazil. Half of species recognized here are known only for the female. The males of N. atromarginata (Cockerell), N. cuprifrons (Smith), N. dilutipes (Vachal), N. erinnys (Schrottky), N. melamptera (Moure), N. roxane (Schrottky) and N. semimarginata (Cockerell) and females of N. iopodion (Vachal) and N. jucunda (Smith) are described for the first time. Identification keys to females and males are presented.